Persistent dyskinesias in patients with fetal tissue transplantation for Parkinson disease - Paul E. Greene (Nature Portfolio, 2021)
Abstract Cell transplants are being developed for patients with Parkinson disease (PD) who have insufficient benefit with standard medical treatment. We describe the clinical features of five patients who developed persistent dyskinesias after fetal dopaminergic tissue transplantation. All had levodopa-induced dyskinesias preoperatively. We implanted fetal mesencephalic dopaminergic tissue into the putamina bilaterally in 34 patients with advanced PD. They were not immunosuppressed. Five of 34 patients (15%) developed troublesome choreic or dystonic dyskinesias that persisted despite lowering or discontinuing medications. Attempts to treat the involuntary movements with amantadine, clozapine, anticholinergics, dopamine depletors and other medicines had limited success. Metyrosine eliminated dyskinesias but led to the parkinsonian “off” state. Increasing the dose of levodopa worsened the dyskinesias. Three patients required placement of pallidal stimulators, bilaterally in two and unilaterally in one patient who had only contralateral dyskinesias. The two with the bilateral stimulators had improvement in dyskinesias. The patient with the unilateral pallidal stimulator had a substantial reduction of the dyskinesias, but attempts to treat residual “off” symptoms with levodopa were limited by worsening dyskinesias. Although the number of patients developing these persistent dyskinesias was small, these five patients had dramatic improvement after transplant. As a group, they had milder Parkinson signs at baseline and improved to the point of having minimal parkinsonism, with reduction or elimination of levodopa therapy prior to developing persistent dyskinesias. These involuntary movements establish the principle that fetal dopaminergic tissue transplants can mimic the effects of levodopa, not only in reducing bradykinesia, but also in provoking dyskinesias.